Type 2 diabetes management: Patient knowledge and health care team perceptions, South Africa - Nombeko Mshunqane; Aimee V. Stewart; Allan D. Rothberg (AOSIS, 2012)
Background: South African research indicates that the highest death rates between 2004 and 2005 were from diabetes mellitus. There is minimal research information on interactions between what patients know about their disease and what health professionals perceive thatpatients should know to control their disease well.Objectives: This study determined the knowledge that patients with type 2 diabetes have about the management of their disease, as well as the perceptions of the health care team about the services given to patients.Method: Qualitative data were collected using two focus groups and in-depth interviews. Patient focus group (n = 10) explored patients' knowledge about management of type 2 diabetes. Patients were recruited from Dr George Mukhari Hospital outpatients' diabetes clinic. Professional focus group (n = 8) explored the health care team's experiences, barriers and facilitators in managing the disease. Professional focus group participants were recruited because of their expertise in chronic disease management, working in the community (public health) or working directly with patients with type 2 diabetes. Five health care professionals were interviewed using the same guide of questions as for the focus group.Results: Participants identified type 2 diabetes as a chronic disease that needs behaviour change for good control. Five major themes were identified: patients' knowledge; education programmes; behaviour change; support; and a patient-centred approach.Conclusion: Management of type 2 diabetes may be enhanced by reinforcing patients' knowledge, encouraging behaviour change whilst taking into consideration patients' backgrounds. The health care team needs to utilise a patient-centred approach.